Bone Graft Substitutes for Periodontal Use Available in the United States. Issue 4 (1st November 2013) - Avila‐Ortiz, Gustavo; Elangovan, Satheesh; Karimbux, Nadeem
Abstract : A comprehensive search was conducted to identify all the bone substitute products marketed in the United States for periodontal and oral implant applications. Different sources were searched to obtain information regarding the original manufacturer, source, sterilization process, product presentation details, and composition. A detailed report of the results is presented. A total of 144 different bone substitutes were identified. Of those, 93 were allografts, 30 were alloplastic materials, and 21 were xenografts. A multitude of bone graft substitutes are currently available in the United States for periodontal and oral implant applications and the majority are allografts produced by well‐established tissue banks or manufacturers.